"*Pseudonyms Are Used Throughout": A Footnote, Unpacked. (January 2022) - Heaton, Janet
Pseudonyms are often used to de-identify participants and other people, organizations and places mentioned in interviews and other textual data collected for research purposes. While this is commonplace, the rationale for, and limits of, using pseudonyms or other methods to disguise identifying information are seldom explained in empirical works. Following an illustrated outline of pseudonyms, epithets, codenames and other obscurant techniques used in the social sciences and humanities, this paper considers how they variously frame the identities of, and position the relations between, participants and researchers. It suggests ways in which researchers might improve on current practice.